The possible effect of high magnetic fields on the aqueous corrosion behaviour of Eurofer - Burrows, R; Baron-Wiechec, A; Harrington, C; Moore, S; Chaney, D; Martin, T; Likonen, J; Springell, R; Surrey, E (Elsevier, 2018)
In defining the corrosion control requirements for DEMO, the impact of the mixed Eurofer-97/AISI 316 steel system and plant specific effects should be considered throughout, in particular, the effect of the intense magnetic fields present. A substantial amount of data related to corrosion resistance of structural materials is available for industrial applications in fission, but applies to different materials and neutronic conditions. Experimental work is being carried out under the DEMO Breeding Blanket Project of the EUROfusion programme, which will further develop the understanding of irradiation effects. However, there is very limited information regarding magnetic field-assisted corrosion under conditions relevant for the fusion environment readily available in the literature. This work reviews current knowledge and progress in establishing the possible influence of the intense magnetic field on corrosion behaviour of the main structural material, Eurofer-97, in the breeding blanket. To support the relevance of this problem statement, preliminary corrosion experimental results of Eurofer-97 coupons, obtained by using a simple apparatus that allows exposure to a magnetic field intensity of 0.88 T and temperatures up to 80 °C in water at atmospheric pressure, are presented as an initial qualitative investigation of possible magnetic field related effects.